2000
DOI: 10.1121/1.429428
|View full text |Cite
|
Sign up to set email alerts
|

Localization of amplitude-modulated high-frequency noise

Abstract: This study investigated whether listeners can use interaural time differences ͑ITDs͒ in the amplitude envelope to localize high-frequency sounds in a free field. Localization accuracy was measured for high-frequency ͑7 to 14 kHz͒ noise with and without an imposed amplitude modulation ͑AM͒ at 20, 80 or 320 Hz. Only AM at 320 Hz led to more accurate localization relative to the nonmodulated condition. The results of a control experiment suggest that the improvement in localization accuracy was due to an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
2
13
1
Order By: Relevance
“…It is unlikely that microsecond envelope ITDs at the onsets and/or offsets of the noise bursts used in the present study could be used for sound source localization given that all stimuli were presented with 20-ms rise/fall times. Eberle et al (2000) have shown that it is highly unlikely that listeners use ongoing ITDs in the envelope of broadband stimuli (similar to ones used in the present study) in sound source localization in the free-field. These data and the use of 20-ms rise-fall times make it unlikely that the listeners in the present study used envelope-ITD cues as a basis for sound source localization.…”
Section: Discussionmentioning
confidence: 93%
“…It is unlikely that microsecond envelope ITDs at the onsets and/or offsets of the noise bursts used in the present study could be used for sound source localization given that all stimuli were presented with 20-ms rise/fall times. Eberle et al (2000) have shown that it is highly unlikely that listeners use ongoing ITDs in the envelope of broadband stimuli (similar to ones used in the present study) in sound source localization in the free-field. These data and the use of 20-ms rise-fall times make it unlikely that the listeners in the present study used envelope-ITD cues as a basis for sound source localization.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore the benefit from modulation in reverberation in the side region may result from directional localization ability being impaired in the side region. Eberle et al (2000), which did not separate azimuth judgments by region, found modulation decreased angular error for very high modulation frequencies, but believe it was due to the sidebands increasing the bandwidth of the stimuli. In the present experiment, the modulation rate was not high enough for sidebands to increase the stimulus bandwidth.…”
Section: Front-back Reversal Analysesmentioning
confidence: 88%
“…Azimuth judgments were compared between conditions using a measure of angular error which has been used in past sound directional localization studies (Wightman & Kistler, 1989b;Eberle et al, 2000). Wightman and Kistler's (1989b) listeners were very accurate localizing sounds over headphones with a mean angular error of 19°, however their stimuli were generated using individualized HRTFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations